Structure of Arabidopsis leaf starch is markedly altered following nocturnal degradation. (6th March 2015) - Zhu, Fan; Bertoft, Eric; Wang, You; Emes, Michael; Tetlow, Ian; Seetharaman, Koushik
Highlights: Analytical paradigm on storage starch used for transitory starch. Cluster structure of transitory starch is revealed. Diurnal impact on transitory starch structure is explored. Abstract: Little is known about the thermal properties and internal molecular structure of transitory starch. In this study, granule morphology, thermal properties, and the cluster structure of Arabidopsis leaf starch at beginning and end of the light period were explored. The structural properties of building blocks and clusters were evaluated by using diverse chromatographic techniques. On the granular level, starch from end of day had larger granule size, thinner crystalline lamellae thickness, lower free surface energy of crystals, and lower tendency to retrograde than that from end of night. On the molecular level, the starch had lower amylose content, larger cluster size, and higher number of blocks per cluster at the end of day than at end of night. It is concluded that the core of the granules contains a more permanent molecular and less-ordered physical structure different from the transitory layers laid down around the core at daytime.